2016
DOI: 10.1093/fampra/cmw058
|View full text |Cite
|
Sign up to set email alerts
|

‘Parallel universes’? The interface between GPs and dentists in primary care: a qualitative study

Abstract: Except in cases of personal contact, interaction between GPs and dentists is often limited and sometimes difficult-despite numerous inter-professional issues. Interdisciplinary approaches in continuing education, medical and dental school teaching and guideline development are potentially promising for promoting cooperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Notwithstanding, this study found that the evidence for the bidirectional relationship between diabetes and periodontitis was valued by medical clinicians, and informing patients was considered legitimate by the medical team, particularly to the role of nurses [21]. As difficulties with collaborative working between dental and medical clinicians have been reported previously in the literature [22,23], and dissemination of guidelines alone is insufficient in promoting a change in clinical practice [24], this study aimed to explore potential ways to enable improved inter-professional working as outlined in extant diabetes and periodontitis guidance documents.…”
Section: Aap Americanmentioning
confidence: 64%
See 2 more Smart Citations
“…Notwithstanding, this study found that the evidence for the bidirectional relationship between diabetes and periodontitis was valued by medical clinicians, and informing patients was considered legitimate by the medical team, particularly to the role of nurses [21]. As difficulties with collaborative working between dental and medical clinicians have been reported previously in the literature [22,23], and dissemination of guidelines alone is insufficient in promoting a change in clinical practice [24], this study aimed to explore potential ways to enable improved inter-professional working as outlined in extant diabetes and periodontitis guidance documents.…”
Section: Aap Americanmentioning
confidence: 64%
“…Miscommunication between dental and medical clinicians has previously been reported elsewhere in the literature. A study of German GPs and GDPs showed problematic collaborative working with allegations of poor knowledge, uncertainty of role and previous difficult interactions [23]. Holzinger et al also reported GPs' frustration relating to requests from GDPs for advice on anticoagulant therapy and dose adjustment for dental procedures, suggesting that this practice is widespread [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of general practitioners saw no need for medical‐dental collaboration, although dentists were interested in extending medical‐dental collaboration . Another qualitative study showed that general practitioners and dentists perceived knowledge deficits in other specialty and frequently criticized aspects of each other's patient management . Furthermore, interaction between general practitioners and dentists is often limited except in cases of personal contact .…”
mentioning
confidence: 99%
“…Another qualitative study showed that general practitioners and dentists perceived knowledge deficits in other specialty and frequently criticized aspects of each other's patient management . Furthermore, interaction between general practitioners and dentists is often limited except in cases of personal contact . Medical‐dental collaboration is inadequate and should be improved in general and family medicine.…”
mentioning
confidence: 99%